Analisis Kekuatan dan Ekspansi Volume Tangki Toroidal Penampang Eliptik dengan Beban Internal Pressure - Asnawi Lubis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2014)
In under to reduce the Public Service Obligation (PSO) on oil fuel, the goverment of Indonesia initianted a program of conversion of oil fuel into gas fuel (BBG) for passenger cars. In supporting this program, it is required to develop the component of combustion system. One of the components is strorage tank for BBG that must be carefully designed to avoid burst type failure. Based on previous research, a toroidal tank can withstand higher limit pressure than the PERTAMINA LPG 3kg storage tank used nowadays in Indonesia household. The present study was exstended to toroidal tank of elliptic cross-section. The strength in term of limit pressure was evaluated numerically using the ANSYS 13 finite element software. The ANSYS SHELL 181 element type was used. Limit pressure were obtained via nonlinier analysis using the well-known Newton-Raphson algorithm, and corresponding stress and strain were evaluated. The results show that toroidal tank having elliptic ratio (a/b) of 1.0 (circular) can withstand highest limit pressure, both for in-plane and out-of-plane elliptic, i.e.,1.16 times the pressure to yield (py). Attachment of a nozzle on intrados position results in reducing the limit pressure by 5.21%, becomes 1.1 py. The result of corresponding volume expansion when the limit pressure was reached is 0.337 % of the initial volume. It is interesting to note that limit pressure become lower than the pressure to yield when the ratio of major to minor axis of the ellip higher than 1.4. In conclusion. the value of ellipticity a/b must not be higher than 1.4 for further development of a toroidal tank. keywords: toroidal, in-plane elliptic, out-of-plane elliptic, limit pressure, volume expansion